Administrative Regulation of Property Rights Agricultural Lands as a Model - Mageed, Elaf; Qaddouri, Tagreed (Journal of Legal Sciences, 2026)
The right to property is considered one of the most important original real rights. Its originality lies in the fact that it is a comprehensive and exclusive right, as the right of ownership grants the owner powers over the property that no one else enjoys. It is one of the most significant individual rights and the most expansive in scope, recognized in most positive legal systems and declarations of rights, though its extent and scope may vary in terms of quantity and quality based on the social, economic, and political philosophy underpinning the legal system of each country. Due to the inherent importance of the right to property, legal perspectives on it have varied over time. Initially, it was viewed as an absolute right with no restrictions, but later, attention shifted toward seeing it as a social function. Additionally, there is an argument that the right to property serves a social function, not that it is inherently a social function in itself. Despite the various views on this matter in different countries, the imposition of restrictions on property rights over time cannot be denied. Scholars have long acknowledged the social function of property, and since one of the primary functions of the state is to maintain public order in society, this concept has played a crucial role in imposing limitations on property rights. A review of international agreements, declarations of rights, and modern constitutions across different countries reveals that they recognize the right to private property and provide it with the necessary protection. However, they also acknowledge that legislation can impose restrictions on it to fulfill the social function of private property. The absolute nature that once accompanied the right to property, or the freedom to own the object of the right, no longer aligns with the developments in the role of the state and the interventionist character necessitated by recent developments. Therefore, private property—both movable and immovable—has been subject to restrictions imposed by administrative control, such as those placed on the ownership of agricultural land